PENGARUH STRUKTUR KEPEMILIKAN DAN KINERJA KEUANGAN TERHADAP KEBIJAKAN DIVIDEN - Mona Kartika, Ni Putu Silva; Suarjaya, Anak Agung Gede (E-Jurnal Manajemen, 2015)
800x600 This study was to determine the effect the structure of institutional ownership, managerial ownership structure and financial performance on dividend policy. The population in this study is a manufacturing company in Indonesia Stock Exchange that has the institutional ownership, managerial ownership, and dividends four years in a row during the observation period 2010-2013 as many as 15 companies were examined as a whole ( sample saturated ) using analytical techniques multiple linear regression and partial test . The results showed that the structure of institutional ownership a significant negative effect on dividend policy, while the ownership structure of managerial and financial performance significant positive effect on dividend policy. Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif";}
Keywords: structure of institutional ownership, managerial ownership structure of financial performance , dividend policy